A Discrete New Generalized Two Parameter Lindley Distribution: Properties, Estimation and Applications - Salem, Manal M.; Ismail, Moshira A. (Statistics, Optimization & Information Computing, 2023)
In this paper, a discrete new generalized two parameter Lindley distribution is proposed. Discrete Lindley and Geometric distributions are sub-models of the proposed distribution. Its probability mass function exhibits different shapes including decreasing, unimodal and decreasing-increasing-decreasing. Our proposed distribution has only two-parameters and its hazard rate function can accommodate increasing, constant, decreasing and bathtub shapes. Moreover, this distribution can describe equi and over dispersed data. Several distributional properties are obtained and several reliability characteristics are derived such as cumulative distribution function, hazard rate function, second hazard rate function, mean residual life function, reverse hazard rate function, accumulated hazard rate function and also its order statistics. In addition, the study of the shapes of the hazard rate function is provided analytically and also by plots. Estimation of the parameters is done using the maximum likelihood method. A simulation study is conducted to assess the performance of the maximum likelihood estimators. Finally, the flexibility of the model is illustrated using three real data sets.